X-ray absorption and emission spectroscopic studies of BiMn2-xTixO5 (0 <= x <= 0.5) - Thakur, P.; Chae, K. H.; Whang, C. N.; Chang, G. S.; Shukla, D. K.; Mollah, S.; Kumar, Ravi (KOREAN PHYSICAL SOC, 2008)
The electronic structure of the multiferroic BiMn2-xTixO5(0 <= x <= 0.5) system was studied by using X-ray absorption spectroscopy (XAS) and X-ray emission spectroscopy (XES). The polycrystalline bulk BiMn2-xTixO5 samples were synthesized using a conventional solid-state reaction technique. XAS and XES spectroscopic studies on the O K-, Mn K-, L-3,L-2- and Ti L-3,L-2-edges of the BiMn2-xTixO5 samples and of the reference compounds were performed and the results were compared in order to determine the exact chemical states of functioning ions. The O K-edge XAS and XES results demonstrate a competition between the Mn 3d and the Ti 3d orbitals on hybridizations Mn3+/Mm(4+) with the O 2p orbital. The Mn K- and Mn L-3,L-2-edge XAS spectra, suggest that the ratio increases with increasing Ti doping and drives the system towards octahedral symmetry. On the other hand, Ti ions remain at 4+ states for all compositions, as shown by the Ti L-edge XAS. Here, we present and discuss the detailed electronic structures of the BiMn2-xTixO5 samples.
Keywords: TRANSITION-METAL COMPOUNDS; ELECTRONIC-STRUCTURE; OXIDES; MANGANESE; FIELD